The preoperative evaluation prevent the postoperative complications of thyroidectomy. Issue 1 (March 2015) - Huang, Chien-Feng; Jeng, Yachung; Chen, Kuo-Dong; Yu, Ji-Kuen; Shih, Chao-Ming; Huang, Shih-Ming; Lee, Chen-Hsen; Chou, Fong-Fu; Shih, Ming-Lang; Jeng, Kee-Ching; Chang, Tzu-Ming
Abstract Objective Thyroid surgery is generally a safe surgery but its complications are still common. We wish to identify preoperative factors that predict postoperative complications. Methods A nationwide survey was conducted by senior surgeons from 16 medical centers and 5 regional hospitals in Taiwan to thyroid operations performed over 3 years. 3846 cases were retrospectively examined to identify factors influencing complications: indication for surgery, preoperative evaluation, such as ultrasonography, chest X-ray, computed tomography and magnetic resonance imaging, isotope scanning, fine-needle aspiration cytology (FNAC) and thyroid function test, and patient characteristics. Results Eighty-four percent of patients were female. Seven percent of the patients had immediate postoperative hypocalcemia (mild and severe) and 2.3%, hoarseness (recurrent laryngeal nerve (RLN) injury, temporary/permanent). Logistic regression analysis identified an association between hypocalcemia and RLN injury with age, hospital category, surgical procedure types (total thyroidectomy, unilateral, bilateral subtotal or total resection). A lower incidence of hypocalcemia was related to preoperative neck ultrasound and FNAC analysis (the odds ratio (OR) = 0.5 and 0.65, [95% confidence interval (CI) 0.331–0.768 and 0.459–0.911], P = 0.0014 and 0.0127, respectively), while RLN injury was not associated with any preoperative evaluation. The ORs of hypocalcemia and RLN injury for patients older than 50 years were 0.55 and 2.15, [0.393–0.763 and 1.356–3.4], P < 0.001 and 0.0012, respectively. Conclusions The success of thyroid surgery depends on careful preoperative planning, including a preoperative neck ultrasound to determine the proximity of the nodule to the recurrent laryngeal nerve course, and the consideration of the type of anesthesia, adjuvant devices for intra-op monitoring of the RLN, and surgical modalities. Our results suggest that preoperative evaluation implementations are positively associated with strategy of surgery and postoperative hypocalcemia prevention.